The Health Effects of Gender-Based Violence in Conflict - Shadab Shahali (Journal of Social Behavior and Community Health)
Gender-based violence (GBV) in conflict zones is a widespread and devastating issue with significant implications for the health and well-being of affected populations. As an expert in sexual and reproductive health, the author aims to highlight the multifaceted health effects of GBV during wartime, supported by extensive research and evidence. This editorial will examine the physical, psychological, and social health impacts of GBV in conflict settings, underscoring the urgent need for comprehensive interventions and policy responses. Gender-based violence in war encompasses a range of abuses, including sexual violence, intimate partner violence, and other forms of physical and psychological abuse. These acts are often used as tools of war to terrorize, displace, and control populations. The prevalence of GBV in conflict zones is alarmingly high, with women and girls being disproportionately affected (Goessmann et al.,2020). The physical health consequences of (GBV) in war are severe and complex. Survivors often endure injuries such as genital trauma, fractures, and internal damage, resulting in chronic pain and disability that significantly reduce their quality of life. Additionally, the lack of preventive measures leads to sexually transmitted infections, including HIV, and unwanted pregnancies. Restricted access to healthcare in conflict zones worsens these issues, contributing to higher rates of maternal and infant mortality (Tol et al.,2013). Stigma surrounding STIs further hinders access to treatment and support (Think Global Health,2022). The psychological impact of GBV in war is deep and enduring, with survivors frequently facing mental health issues such as PTSD, depression, and anxiety (World Health Organization ,2014; Carpiniello,2023). The trauma of GBV is exacerbated by continuous stress and instability of living in a conflict zone (Perrin et al.,2019).  PTSD frequently affects survivors of GBV in wartime, manifested as flashbacks, nightmares, and severe anxiety that may last for years after the trauma (World Health Organization ,2014; Carpiniello,2023). Experiencing GBV can result in chronic depression and anxiety, hindering survivors' daily functioning. The absence of mental health services in conflict zones worsens these issues (Tol  et al.,2013).Survivors of GBV frequently experience social stigma and ostracization, resulting in isolation and increased psychological distress. Many refrain from seeking help due to fear of retribution or disbelief (Carpiniello,2023; Perrin et al.,2019). The social health impacts of GBV in war extend beyond individual survivors, affecting families and communities. The breakdown of social structures and the displacement of populations create environments where GBV can thrive, perpetuating cycles of violence and instability(Capasso et al.,2023; World Bank,2024) . GBV can disrupt family dynamics, leading to the breakdown of relationships and the displacement of family members. Children who witness or experience GBV are at risk of long-term psychological and behavioral issues. The prevalence of GBV in conflict zones undermines community cohesion and trust. The fear and trauma associated with GBV can hinder community rebuilding efforts and prolong the recovery process (Perrin et al.,2019). The economic impact of GBV is significant, as survivors may be unable to work or participate in economic activities. The loss of productivity and the cost of healthcare for survivors place additional burdens on already strained resources (World Bank,2024). Addressing the health effects of GBV in war requires a multifaceted approach that includes prevention, protection, and support for survivors. Effective interventions must be grounded in a thorough understanding of the local context and the specific needs of affected populations preventing GBV in conflict zones involves addressing the root causes of violence, including gender inequality and the normalization of violence. Community-based programs that promote gender equality and challenge harmful norms are essential. Protecting survivors of GBV requires the establishment of safe spaces and the provision of legal and medical support. International humanitarian organizations play a crucial role in providing these services in conflict zones. Comprehensive support services for survivors, including medical care, mental health support, and economic assistance, are vital for recovery. These services must be accessible and culturally appropriate to be effective (Capasso et al.,2023; Tol et al.,2013). The health effects of gender-based violence in conflict are profound, affecting individuals, families, and communities. As an expert in sexual and reproductive health, the author stresses the urgent need for comprehensive interventions and policy responses to tackle this issue. By prioritizing prevention, protection, and support for survivors, the devastating health impacts of GBV in conflict zones can be mitigated and a more just and equitable world can be fostered.